The negative factors that are affecting sound financial management practices at the greater Letaba local Municipality in Limpopo Province - Phokanoka, Matawane Hunadi (My University, 2016)
This study mainly focuses on the negative factors that are affecting sound financial practices in the Greater Letaba Local municipality. Greater Letaba municipality fails to achieve a clean audit opinion because of a number of negative factors that affect its sound financial management practices. The municipality partially adheres to financial management policies and legislation which underpin good financial management practices, for example the Auditor General South Africa’s (AGSA) report reflects no adherence to Supply Chain Management (SCM) regulations and also to GRAP standards. These factors include poor record keeping, lack of accountability, none compliance to legislations and poor financial management activities and practices. Audit opinions are either regressing or remaining unchanged and a clean audit is still not achievable at this stage. The municipality’s audit opinion did not change in the past two financial years. The audit opinion remained qualified.The study employed a qualitative research approach whereby interviews wereconducted with Letaba Municipal Officials that are directly involved in financial management practices to collect data. Data were also collected through review of relevant and current literature in the topic under investigation. One of the major findings of the study is that there are a number of vacancies in the critical positions such as in the finance department. The other finding is that the employees do not implement the sound management practices that they are trained for.Therefore, this study recommends that strategies for effective financial management practices should be developed and implemented at Letaba Municipality. Furthermore it investigates the negative factors that are affecting sound financial management in the municipality.
Thesis (MBA.) --University of Limpopo, 2016
Keywords: Financial management; Supply Chain Management; Record keeping; Audit; Finance, Public -- South Africa, Limpopo